Expected benefits and perceived risks of cloud computing: an investigation within an Italian setting. Issue 2 (7th February 2017) - Caldarelli, Adele; Ferri, Luca; Maffei, Marco
ABSTRACT: Over the past several years, cloud computing has increasingly been regarded as able to improve efficiency within organisations. The aim of this study is to address under-investigated issues related to the implementation of cloud computing, with a particular focus on expected benefits and the perception of risks. Towards this aim, on the basis of an adapted version of the technology acceptance model, we carried out a semi-structured survey among first-time cloud computing users to identify expected benefits and perceived risks. The survey of this study included a sample of 130 individuals in 65 enterprises located within Italy. We chose an Italian setting because it is characterised by an increasing number of programmes that emphasise the importance of cloud computing and support its wide dissemination. The findings of this study identify possible areas for improvement within the implementation phases of cloud computing.